EFEKTIFITAS MANAJEMEN JAMA`AH TABLIGH DALAM MENGEMBANGKAN DAKWAH DI KOTA PALU - Ibrahim Latepo; Suharto Suharto (ISTIQRA, 2014)
Management's grown so life there, which starts from the creation of man in which Allah. managing human birth as caliph with clarity and direction to convey his ideas sound off to the angels. Since its inception, Islam has encouraged his community to organize every good work. Management has been implemented in Islam since the age of the prophet. even since the days of the prophets preceding the beginning of Adam in the story of Qabil and Habil marriage arrangements with their wives. With good organization and tidy, will achieve better results than done individually. Institutions will go well, if managed with good and any organization, always in need of management. Management would be more effective, if the functions are applied properly, because the clarity of a management function in a movement or organization, it will be more focused in achieving a goal. Da'wah/preaching as a humanitarian and human movement, it should be clear or necessary a clear management, purposeful and functional. Tabligh community as a missionary movement, it should have a clear objective and perform the functions of preaching rightly